Mapping land cover and vegetation detection in urban areas - Samsuri; Lailan Syaufina; Anggie Yohanna Mandalahi; Zaitunah, Anita (Talenta Publisher, 2022)
The increase of population has caused land use land cover change. The development of a city has increase the need of settlements and buildings. Monitoring any land cover is important to support environmentally based and sustainable urban planning. Medan as one of big cities in Indonesia has showed a development of the areas. The aim of the study was to analyze the land cover and vegetation existence in two sub-districts of Medan. The supervised classification analysis was conducted for year 2019. Ground check was a part of the study. There were six land cover classes found in the area, namely paddy fields, grass, shrubs, trees, mixed plant, and built-up land. The largest area within two sub-districts is built up areas. The results show less vegetated areas within two sub-districts. There was 86% of built-up areas in Medan Baru and 69.3% in Medan Selayang. Vegetation as an important element in the environment needs to be preserved within the urban areas. There is a need to plant trees in less vegetated areas. Green open space should be incorporated into city planning in order to preserve and improve the quality of the urban environment.